Comparative Analysis of Rainfall-Runoff Model Calibration Using Limited Discharge Data in Landak Sub-Watersheds - Teofano, Enrico; Soeryamassoeka, S. B.; Gunarto, Danang (Jurnal Teknik Sipil, 2025)
The limited availability of long-term discharge data remains a significant challenge for rainfall–runoff modeling in Indonesian watersheds, including the Landak Sub-Watershed. This study aims to evaluate the performance of the Mock and Sacramento rainfall–runoff models in simulating river discharge in the Landak Sub-Watershed during the 2022–2023 period. The data used include rainfall, river discharge, and climatological parameters obtained from relevant institutions. The analysis was conducted through model calibration and validation, with model performance evaluated using the correlation coefficient (r) and the RMSE–Standard Deviation of Observations Ratio (RSR). The results show that the Mock model produced moderate correlation coefficients during both the calibration and validation stages (r = 0.64 and 0.65), but with high RSR values, indicating limited agreement with the observed discharge. The Sacramento model demonstrated better performance, with strong calibration (r = 0.73) and moderate validation (r = 0.66), although the RSR values remained high. Overall, both models can represent flow patterns but are not yet capable of accurately reproducing discharge magnitudes due to data limitations and high rainfall variability